Organic electrochemical transistor based on hydrophobic polymer and preparation method and application thereof
By using hydrophobic polymers and doped ion gels in organic electrochemical transistors, the problem of reduced charge transport capability and stability caused by hydrophilic polymers is solved, high transconductance performance and long-term stability are achieved, and high sensitivity and a wide detection range are shown in glucose sensing.
Patent Information
- Application Number
- CN202510263040.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-06-06
AI Technical Summary
Existing electrochemical transistors have shortcomings in transconductance, cyclic testing stability and storage stability, mainly because the hydrophilic chains in hydrophilic conjugated polymers absorb water molecules from the air and trap charges, resulting in reduced charge transport capability and stability.
The synergistic effect of hydrophobic polymers and doped ion gels is adopted to improve the coordinated transmission of electrons and ions, increase the conduction path of electrons, thereby improving transconductance performance. At the same time, the gate electrode is modified to enhance the charge transfer efficiency and device sensitivity of the electrode.
The transconductance performance (57.8 mS) and cycle test stability (30000s) of organic electrochemical transistors are significantly improved, and the device can be stored for a long time (90 days), while achieving high sensitivity, low detection limit and wide detection range detection effects in the field of glucose sensing.
Smart Images

Figure CN120102660A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biosensors, and in particular relates to an organic electrochemical transistor based on a hydrophobic polymer, and a preparation method and application thereof. Background Art
[0002] Organic Electrochemical Transistors (OECTs) are an emerging organic electronic device. Because its dielectric layer is an aqueous solution, it has good biocompatibility and an operating voltage of less than 1 volt. Compared with traditional organic field-effect transistors, it has unique advantages in many fields, especially in the field of biosensing, and has broad application prospects, attracting a lot of scientific research and industrial attention.
[0003] OECTs are usually composed of source / drain electrodes, conjugated polymer films, aqueous electrolyte solutions, and gates. They are three-terminal devices with a conductive channel in a polymer. Unlike organic field-effect transistors, ions in the electrolyte of OECTs can penetrate into the polymer film, producing electrochemical doping throughout the channel, resulting in high transconductance characteristics. Grafting hydrophilic side chains onto polymers can improve ion transport, but requires additional synthesis steps. In addition, the hydrophilic chains in hydrophilic conjugated polymers can absorb water molecules from the air and capture charges, thereby reducing the charge transport capacity. Therefore, although the ion transport of hydrophilic chain-based polymers is improved, the cost is that the charge transport becomes worse.
[0004] CN118812826A discloses the application of a DA-type conjugated polymer in an electrochemical transistor. The polymer is applied to the electrochemical transistor and has high transconductance, cycle test stability and storage stability. Because the DA-type conjugated polymer is a hydrophilic polymer, the maximum transconductance of the electrochemical transistor is only 1.57mS, the cycle test stability is 15000s, and the storage stability is 60 days, and the comprehensive performance is still insufficient. CN116660353A discloses a high-performance organic electrochemical transistor with a foam structure channel prepared based on a template sacrificial method, and its preparation method and application. A hydrophilic PEDOT:PSS film with a foam structure is prepared. Although the transmission of electrons and ions is improved and the transconductance is improved due to the presence of the foam structure, due to the limitations of the hydrophilic polymer itself, the transconductance of the device is only 18mS, and the test time is only 400s. In summary, electrochemical transistors currently still face huge challenges in transconductance, cycle test stability and storage stability. This is because the hydrophilic chains in hydrophilic conjugated polymers can absorb water molecules from the air and capture charges, thereby reducing the charge transfer capacity and stability. Therefore, a polymer that can overcome its shortcomings is needed to improve the overall performance of electrochemical transistors. Summary of the invention
[0005] In view of the deficiencies of the prior art, the present invention provides a highly stable organic electrochemical transistor based on a hydrophobic polymer and its preparation and application. The organic electrochemical transistor is based on the synergistic effect of a high-performance hydrophobic polymer and a doped ion gel, which not only solves the problem that the hydrophilic side chains in the polymer absorb water molecules from the air and capture charges, thereby reducing the charge transfer capacity and stability, resulting in a decrease in the transconductance, cycle test stability and storage stability of the organic electrochemical transistor; it also improves the coordinated transmission of electrons and ions, increases the conduction path of electrons, and improves the transconductance performance during the period. The present invention also modifies the gate electrode to enhance the charge transfer efficiency and device sensitivity of the electrode, and applies the electrochemical transistor based on the modified gate electrode to the field of glucose sensing, so that it has the advantages of high performance, high detection sensitivity and high stability.
[0006] The technical solution of the present invention is an organic electrochemical transistor based on a hydrophobic polymer, comprising a substrate, a source electrode, a drain electrode, a hydrophobic active layer, a doped ion gel layer, an electrolyte layer and a gate, wherein the hydrophobic active layer contains a hydrophobic polymer, and the doped ion gel layer contains a gel polymer, an ionic liquid and a dopant.
[0007] The source and drain are located between the substrate and the hydrophobic active layer, the doped ion gel layer adheres to the hydrophobic active layer, the electrolyte layer contacts the doped ion gel layer and the gate, and the electrolyte layer is further located between the doped ion gel layer and the gate, and contacts the doped ion gel layer and the gate.
[0008] The thickness of the hydrophobic active layer is 30-60 nm.
[0009] The hydrophobic polymers include polydiketopyrrolopyrrole-benzothiadiazole (PDPPBT), poly{2,2'-[(2,5-bis(2-octyldodecyl)-3,6-dioxo-2,3,5,6-tetrahydropyrrolo[3,4-c]pyrrole-1,4-diyl)]dithiophene-5,5'-diyl-alt-2,2'-bithiophene-5,5'-diyl} (PDPP4T), poly[[4,8-bis[5-(2-ethylhexyl)-4-fluoro-2-thienyl]benzo[1,2-B:4,5-B'-dithiophene-2,6-diyl]-2,5-thiophenediyl][5,7-bis(2-ethylethylhexyl)-4,8-dioxo-4H,8H-benzo[1,2 -C:4,5-C'-]dithiophene-1,3-diyl]-2,6-thiophenediyl] (PM6), polyindenodithiophene-benzothiadiazole (IDT-BT), poly[(1,2,5-thiadiazo[3,4-c]pyridine-4,7-diyl)(4,4-diahexanoyl-4H-cyclopenta[2,1-b:3,4-b']dithiophene-2,6-diyl)(1,2,5-thiadiazo[3,4-c]pyridine-4,7-diyl)(4,4-diahexanoyl-4H-cyclopenta[2,1-b:3,4-b']dithiophene-2,6-diyl)] (PCDTPT), any one or any combination thereof, preferably polydiketopyrrolopyrrole-benzothiadiazole (PDPPBT).
[0010] The mass ratio of the gel polymer to the dopant in the doped ion gel layer is 1200-30:1, preferably 500-90:1, and more preferably 100-150:1; the dosage ratio of the gel polymer to the ionic liquid is 300-400 mg:1 ml, preferably 360-365 mg:1 ml; the concentration of the ionic liquid is greater than 95%, preferably greater than 99%. The gel polymer is poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), the dopant is (2,3,5,6-tetrafluoro-2,5-cyclohexadiene-1,4-diylidene) dimalononitrile, and the ionic liquid is 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl) (BMIM TFSI) and / or 1-ethyl-3-methylimidazole bis(fluoromethylsulfonyl)imide (EMIM TFSI).
[0011] The doped ion gel layer further contains bis(trifluoromethylsulfonyl)imide salt, and the mass ratio of bis(trifluoromethylsulfonyl)imide salt to gel polymer is 0.8-1.5:1, preferably 1:1. The bis(trifluoromethylsulfonyl)imide salt includes but is not limited to bis(trifluoromethylsulfonyl)imide lithium (Li TFSI), tris(trifluoromethanesulfonyl)imide aluminum (Al(TFSI) 3 ), tris(bis(trifluoromethanesulfonyl)imide aluminum iron (Fe(TFSI)3 ), magnesium bis(trifluoromethanesulfonyl)imide (Mg(TFSI) 2 ), Zinc bis(trifluoromethanesulfonyl)imide (Zn(TFSI) 2 ), preferably lithium bis(trifluoromethylsulfonyl)imide (Li TFSI).
[0012] The electrolyte layer contains NaCl, KCl, FeCl 2 、FeCl 3 MgCl 2 , PBS and other electrolytes, preferably NaCl; the concentration of the electrolyte is 0.1 mol / L.
[0013] The substrate includes polyethylene terephthalate (PET), Si / SiO 2 , glass, preferably polyethylene terephthalate (PET).
[0014] The source electrode and the drain electrode are made of any one or any combination of gold, silver and chromium, preferably gold; the thickness of the source electrode and the drain electrode ranges from 30 to 100 nm, preferably 60 nm.
[0015] The gate is made of any one or any combination of gold, silver and platinum, preferably gold; the thickness of the gate is 30-100nm, preferably 60nm.
[0016] When applied to glucose sensing, the gate is coated with PDPPBT doped with nanoparticles, drop-cast glucose oxidase GOx and drop-cast Nafion in sequence.
[0017] The mass ratio of the nanoparticles to the PDPPBT doped with nanoparticles is 1.5-4:1, preferably 2:1; the nanoparticles are MnO 2 Nanoparticles, particle size is 100-150nm.
[0018] The dosage of the glucose oxidase GOx is 0.1-1 mg, preferably 0.4-0.5 mg.
[0019] The amount of Nafion used is 8-15 μl of a 5% by mass Nafion solution, preferably 10-15 μl.
[0020] The present invention provides a method for preparing an organic electrochemical transistor based on a hydrophobic polymer, the steps comprising:
[0021] S1: Using vacuum deposition method, evaporate the source and drain electrodes on the surface of the substrate;
[0022] S2: Spin-coating a hydrophobic polymer solution on the source and drain electrodes, and heat treating the solution to obtain a hydrophobic active layer;
[0023] S3: mixing the gel polymer, the ionic liquid and the dopant in an organic solvent, and heat treating the mixture to obtain a doped ion gel layer; adhering the doped ion gel layer to the hydrophobic active layer prepared in step 2 to obtain a device;
[0024] S4: using vacuum deposition method to evaporate the gate;
[0025] S5: placing the device prepared in step S3 and the gate prepared in step S4 in an electrolyte.
[0026] In S1, the substrate includes polyethylene terephthalate (PET), Si / SiO 2 , glass, preferably polyethylene terephthalate (PET). When the substrate is polyethylene terephthalate or glass, it is ultrasonically rinsed with deionized water, acetone, and isopropanol in sequence, then blown dry with nitrogen, and finally heated and dried at 70°C-85°C. The ultrasonic times are twice, and the ultrasonic time each time is 10-20 minutes, preferably 10 minutes. The substrate is Si / SiO 2 When the substrate is washed, it is washed with deionized water, concentrated sulfuric acid-hydrogen peroxide mixed solution (the volume ratio of concentrated sulfuric acid to hydrogen peroxide is 2:1), deionized water, and isopropanol in turn, then blown dry with nitrogen, and finally heated and dried at 70℃-85℃. Concentrated sulfuric acid and hydrogen peroxide are mixed in a volume ratio of 2:1 and then soaked in the cup wall and cooled to room temperature for washing.
[0027] In S1, an inorganic vacuum evaporator is used, and the evaporation rate is The source electrode and the drain electrode are made of any one or any combination of gold, silver and chromium, preferably gold; the thickness of the source electrode and the drain electrode is in the range of 30-100 nm, preferably 60 nm.
[0028] In S2, the concentration of the hydrophobic polymer solution is 4-10 mg / ml, preferably 4-5 mg / ml. The hydrophobic polymers include polydiketopyrrolopyrrole-benzothiadiazole (PDPPBT), poly{2,2'-[(2,5-bis(2-octyldodecyl)-3,6-dioxo-2,3,5,6-tetrahydropyrrolo[3,4-c]pyrrole-1,4-diyl)]dithiophene-5,5'-diyl-alt-2,2'-bithiophene-5,5'-diyl} (PDPP4T), poly[[4,8-bis[5-(2-ethylhexyl)-4-fluoro-2-thienyl]benzo[1,2-B:4,5-B'-dithiophene-2,6-diyl]-2,5-thiophenediyl}(PDPP4T), poly[[4,8-bis[5-(2-ethylhexyl)-4-fluoro-2-thienyl]benzo[1,2-B:4,5-B'-dithiophene-2,6-diyl]-2,5-thiophenediyl} :4,5-C'-]dithiophene-1,3-diyl]-2,6-thiophenediyl] (PM6), polyindenodithiophene-benzothiadiazole (IDT-BT), poly[(1,2,5-thiadiazo[3,4-c]pyridine-4,7-diyl)(4,4-diahexanoyl-4H-cyclopenta[2,1-b:3,4-b']dithiophene-2,6-diyl)(1,2,5-thiadiazo[3,4-c]pyridine-4,7-diyl)(4,4-diahexanoyl-4H-cyclopenta[2,1-b:3,4-b']dithiophene-2,6-diyl)] (PCDTPT), any one or any combination thereof, preferably polydiketopyrrolopyrrole-benzothiadiazole (PDPPBT). The solvent used for preparing the hydrophobic polymer solution is any one or any combination of chloroform, chlorobenzene and toluene, preferably chloroform.
[0029] In S2, the coating is performed on a coating machine at a rotation speed of 2000-4000 r / min, and the coating time is 20-30 s.
[0030] In S2, heat treatment is performed at 70°C-85°C.
[0031] In S3, the concentration of the gel polymer in the organic solvent is 50-200 mg / ml, preferably 75-80 mg / ml; the mass ratio of the gel polymer to the dopant is 1200-30:1, preferably 500-90:1, more preferably 100-150:1; the amount ratio of the gel polymer to the ionic liquid is 300-400 mg:1 ml, preferably 360-365 mg:1 ml; the concentration of the ionic liquid is greater than 95%, preferably greater than 99%. The organic solvent includes but is not limited to any one or any combination of acetone, xylene, dimethyl sulfoxide, isopropanol, and ethyl acetate, preferably acetone. The gel polymer is poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), the dopant is (2,3,5,6-tetrafluoro-2,5-cyclohexadiene-1,4-diylidene) dimalononitrile, and the ionic liquid is 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl) (BMIM TFSI) and / or 1-ethyl-3-methylimidazole bis(fluoromethylsulfonyl)imide (EMIM TFSI).
[0032] In S3, the organic solvent further contains a bis(trifluoromethylsulfonyl)imide salt, and the mass ratio of the bis(trifluoromethylsulfonyl)imide salt to the gel polymer is 0.8-1.5:1, preferably 1:1. The bis(trifluoromethylsulfonyl)imide salt includes but is not limited to lithium bis(trifluoromethylsulfonyl)imide (Li TFSI), aluminum tris(trifluoromethanesulfonyl)imide (Al(TFSI) 3 ), tris(bis(trifluoromethanesulfonyl)imide aluminum iron (Fe(TFSI) 3 ), magnesium bis(trifluoromethanesulfonyl)imide (Mg(TFSI) 2 ), Zinc bis(trifluoromethanesulfonyl)imide (Zn(TFSI) 2 ), preferably lithium bis(trifluoromethylsulfonyl)imide (Li TFSI).
[0033] In S3, the gel polymer is first dissolved in an organic solvent, the ionic liquid is then added and mixed, and finally the dopant is added and mixed. When the organic solvent contains bis(trifluoromethylsulfonyl)imide salt, the bis(trifluoromethylsulfonyl)imide salt is added before the ionic liquid is added.
[0034] In S3, heat treatment is performed at 45°C-50°C.
[0035] In S4, an inorganic vacuum evaporator is used, and the evaporation rate is The material of the gate is any one or any combination of gold, silver and chromium, preferably gold; the thickness of the gate is in the range of 30-100 nm, preferably 60 nm.
[0036] When applied to glucose sensing, in S4, a solution of doped nanoparticles and PDPPBT is spin-coated on the gate and heat-treated at 80°C-90°C; then a glucose oxidase aqueous solution is drop-cast and heat-treated at 35°C-45°C; finally, a Nafion solution is drop-cast and heat-treated at 35°C-45°C to prepare a gate electrode modified with PDPPBT doped nanoparticles / GOx / Nafion.
[0037] The total concentration of the nanoparticles and PDPPBT is 10-15 mg / ml, preferably 12 mg / ml; the mass ratio of the nanoparticles to PDPPBT is 1.5-4:1, preferably 2:1; the solvent is any one or any combination of chloroform, dichloromethane, and ethyl acetate, preferably chloroform; the nanoparticles are MnO 2 Nanoparticles, particle size is 100-150nm.
[0038] The concentration of the glucose oxidase aqueous solution is 15-30 mg / ml, preferably 20 mg / ml; the dosage is 10-30 μl, preferably 18-23 μl.
[0039] The concentration of the Nafion solution is not less than 5%, preferably 5%; the dosage is 5-30 μl, preferably 10-15 μl.
[0040] In S5, the electrolyte includes NaCl, KCl, FeCl 2 、FeCl 3 MgCl 2 , PBS and other electrolytes, preferably NaCl, and the concentration of the electrolyte is 0.1 mol / L.
[0041] The organic electrochemical transistor prepared as described above can be used to prepare a sensor, especially a glucose detection sensor, for the qualitative and / or quantitative detection of glucose.
[0042] The present invention provides a sensor, which contains the organic electrochemical transistor prepared by the present invention.
[0043] The present invention provides a method for qualitative and / or quantitative detection of glucose, comprising the following steps: placing the organic electrochemical transistor or sensor prepared by the present invention in a buffer solution not containing glucose, recording the response of the source and drain electrodes, then adding a sample solution, recording the response changes of the source and drain electrodes, and performing qualitative and / or quantitative detection of glucose.
[0044] The buffer solution includes but is not limited to PBS buffer solution, Tris-HCl buffer solution, EDTA buffer solution, etc., preferably PBS buffer solution.
[0045] Compared with the prior art, the present invention has the following advantages:
[0046] 1. A high-stability organic electrochemical transistor based on a hydrophobic polymer prepared by the present invention uses a high-performance hydrophobic polymer to solve the problem that the hydrophilic side chains in the polymer can absorb water molecules from the air and capture charges, thereby reducing the charge transfer capacity and stability, resulting in a decrease in the transconductance, cycle test stability and storage stability of the organic electrochemical transistor. The electrochemical transistor based on the hydrophobic polymer greatly improves the transconductance performance (57.8mS) and the cycle test stability of the device operation (30000s), and the device can be stored for a long time (90 days). Compared with the conventional optimization methods such as changing the semiconductor film morphology and adding a new organic semiconductor doping layer, the high-stability organic electrochemical transistor based on the hydrophobic polymer provided by the present invention has the outstanding advantages of high performance, high stability, low cost and simple process.
[0047] 2. The high-stability organic electrochemical transistor based on hydrophobic polymer prepared by the present invention can be applied to the field of glucose detection. After simple modification of the gate electrode, the charge transfer efficiency of the electrode and the device sensitivity are enhanced, and the device can detect glucose concentration with high sensitivity, low detection limit (1nM), and wide detection range (1nM-10mM). BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 It is a schematic diagram of the structure of the present invention; wherein 1 is a substrate layer, 2 is a source electrode, 3 is a drain electrode, 4 is an active layer, 5 is a doped ion gel layer, 6 is an electrolyte layer, and 7 is a gate electrode.
[0049] Figure 2 This is a test graph of the water contact angle of the polymer used in Examples 2-6 of the present invention.
[0050] Figure 3 The transfer characteristic curve and transconductance curve of the organic electrochemical transistor prepared in Example 4 of the present invention.
[0051] Figure 4 This is the output curve of the organic electrochemical transistor prepared in Example 4 of the present invention.
[0052] Figure 5 This is a schematic diagram of the performance of the organic electrochemical transistor prepared in Example 4 of the present invention after 30,000 seconds of cycling.
[0053] Figure 6 This is a graph showing the change in transconductance of the organic electrochemical transistor prepared in Example 4 of the present invention after being stored for 90 days.
[0054] Figure 7 This is a source-drain current curve of the organic electrochemical transistor sensor prepared in Example 7 of the present invention when detecting ultra-low glucose concentration. DETAILED DESCRIPTION
[0055] In order to more clearly illustrate the purpose and advantages of the present invention, the present invention is further described in detail with reference to the following embodiments in conjunction with the accompanying drawings. The specific embodiments described below are only used to explain the present invention and are not used to limit the present invention.
[0056] Example 1
[0057] This embodiment provides a method for preparing an organic electrochemical transistor based on a hydrophilic polymer, and the specific steps are as follows:
[0058] 1. Cut the PET substrate into 10*20mm size and put it into the cleaned beaker, rinse it with deionized water twice, and ultrasonicate it for 10 minutes, then rinse it with acetone once and ultrasonicate it for 10 minutes, then rinse it with isopropanol once and ultrasonicate it for 10 minutes, finally blow it dry with a nitrogen gun, and heat and dry it at 80℃ for 30 minutes.
[0059] 2. Use vacuum deposition to deposit 60nm thick Au on the cleaned PET as source and drain electrodes at a deposition rate of
[0060] 3. Prepare a 4 mg / ml aqueous solution of the hydrophilic polymer PEDOT:PSS, then spin-coat 20 μl onto the prepared electrode at 2000 r / min, and heat it in a vacuum oven at 80°C for 2 h to obtain an active layer.
[0061] 4. Add 300 mg of PVDF-HFP into a glass bottle containing 3 ml of acetone, heat at 40°C with a magnetic stirrer at 1000 r / min for 2 h to make it dissolve evenly, then add 832 μl of BMIM TFSI solution with a concentration greater than 99%, and continue stirring at 1000 r / min for 1.5 h. Pour the prepared mixed liquid into a glass dish with a diameter of 35 mm, wrap it with tin foil, place it on a heating table, heat at 45°C for 12 h to gel, and obtain an undoped ion gel layer, which is then adhered to the active layer obtained in step 3 with organic silica gel.
[0062] 5. Prepare a NaCl solution with a concentration of 0.1 mol / L, with water as the solvent, and place the device spin-coated in step 4 into the solution.
[0063] 6. Evaporate 60nm thick Au as the gate electrode and insert it into the electrolyte.
[0064] 7. Use a semiconductor analysis tester to test the performance of the device, set the drain voltage to -0.5V, and the gate voltage to 0.2V~-1V. The device performance obtained by the test is: transconductance g m =17.85mS, threshold voltage V t =0.77V, switch off Ion / off =6.8×10 3 , and the device cannot be stored for a long time.
[0065] Example 2
[0066] This embodiment provides a method for preparing an organic electrochemical transistor based on a hydrophobic polymer, and the specific steps are as follows:
[0067] 1. Cut the PET substrate into 10*20mm size and put it into the cleaned beaker, rinse it with deionized water twice, and ultrasonicate it for 10 minutes, then rinse it with acetone once and ultrasonicate it for 10 minutes, then rinse it with isopropanol once and ultrasonicate it for 10 minutes, finally blow it dry with a nitrogen gun, and heat and dry it at 80℃ for 30 minutes.
[0068] 2. Use vacuum deposition to deposit 60nm thick Au on the cleaned PET as source and drain electrodes at a deposition rate of
[0069] 3. Place the hydrophobic polymer PDPPBT in a glass bottle filled with chloroform and stir to prepare a solution with a concentration of 4 mg / ml to make it dissolve evenly. Then spin coat 20 μl of it on the prepared electrode at 2000 r / min and heat it in a vacuum oven at 80°C for 2 h to obtain an active layer.
[0070] 4. Add 300 mg of PVDF-HFP into a glass bottle containing 3 ml of acetone, heat at 40°C with a magnetic stirrer at 1000 r / min for 2 h to make it dissolve evenly, then add 832 μl of BMIM TFSI solution with a concentration greater than 99%, and continue stirring at 1000 r / min for 1.5 h. Pour the prepared mixed liquid into a glass dish with a diameter of 35 mm, wrap it with tin foil, place it on a heating table, heat at 45°C for 12 h to gel, and obtain an undoped ion gel layer, which is then adhered to the active layer obtained in step 3 with organic silica gel.
[0071] 5. Prepare a NaCl solution with a concentration of 0.1 mol / L, with water as the solvent, and place the device spin-coated in step 4 into the solution.
[0072] 6. Evaporate 60nm thick Au as the gate electrode and insert it into the electrolyte.
[0073] 7. Use a semiconductor analysis tester to test the performance of the device, set the drain voltage to -0.5V, and the gate voltage to 0.2V~-1V. The device performance obtained by the test is: transconductance g m =35.1mS, threshold voltage V t =0.74V, switch off I on / off =2.19×10 4, and the device cannot be stored for a long time.
[0074] Example 3
[0075] This embodiment provides a method for preparing an organic electrochemical transistor based on a hydrophobic polymer. The difference from Example 2 is that the traditional ion gel is replaced with a doped ion gel. The specific steps are as follows:
[0076] 1. Cut the PET substrate into 10*20mm size and put it into the cleaned beaker, rinse it with deionized water twice, and ultrasonicate it for 10 minutes, then rinse it with acetone once and ultrasonicate it for 10 minutes, then rinse it with isopropanol once and ultrasonicate it for 10 minutes, finally blow it dry with a nitrogen gun, and heat and dry it at 80℃ for 30 minutes.
[0077] 2. Use vacuum deposition to deposit 60nm thick Au on the cleaned PET as source and drain electrodes at a deposition rate of
[0078] 3. Place the hydrophobic polymer PDPPBT in a glass bottle filled with chloroform and stir to prepare a solution with a concentration of 4 mg / ml to make it dissolve evenly. Then spin coat 20 μl of it on the prepared electrode at 2000 r / min and heat it in a vacuum oven at 80°C for 2 h to obtain an active layer.
[0079] 4. Add 300 mg of PVDF-HFP to a glass bottle containing 3 ml of acetone and heat at 40°C with a magnetic stirrer at 1000 r / min for 2 hours to make it dissolve evenly, then add 832 μl of BMIM TFSI solution with a concentration greater than 99%, continue stirring at 1000 r / min for 1.5 hours, add 0.3 mg of (2,3,5,6-tetrafluoro-2,5-cyclohexadiene-1,4-diylidene) dimalononitrile to the solution and stir at 1000 r / min for 2 hours. Pour the prepared mixed liquid into a glass dish with a diameter of 35 mm, wrap it with tin foil, place it on a heating table and heat it at 45°C for 12 hours to gel, and obtain a doped ion gel layer, which is then adhered to the active layer obtained in step 3 with organic silica gel.
[0080] 5. Prepare a NaCl solution with a concentration of 0.1 mol / L, with water as the solvent, and place the device spin-coated in step 4 into the solution.
[0081] 6. Evaporate 60nm thick Au as the gate electrode and insert it into the electrolyte.
[0082] 7. Use a semiconductor analysis tester to test the performance of the device, set the drain voltage to -0.5V, and the gate voltage to 0.2V~-1V. The device performance obtained by the test is: transconductance g m =43mS, threshold voltage Vt =0.59V, switch off I on / off =2.24×10 5 , and the device can be stored for a short period of time.
[0083] Example 4
[0084] This embodiment provides a method for preparing a high-stability organic electrochemical transistor based on a hydrophobic polymer. The difference from Example 3 is that the dosage of the dopant is adjusted to 3 mg. The specific steps are as follows:
[0085] 1. Cut the PET substrate into 10*20mm size and put it into the cleaned beaker, rinse it with deionized water twice, and ultrasonicate it for 10 minutes, then rinse it with acetone once and ultrasonicate it for 10 minutes, then rinse it with isopropanol once and ultrasonicate it for 10 minutes, finally blow it dry with a nitrogen gun, and heat and dry it at 80℃ for 30 minutes.
[0086] 2. Use vacuum deposition to deposit 60nm thick Au on the cleaned PET as source and drain electrodes at a deposition rate of
[0087] 3. Place the hydrophobic polymer PDPPBT in a glass bottle filled with chloroform and stir to prepare a solution with a concentration of 4 mg / ml to make it dissolve evenly. Then spin coat 20 μl of it on the prepared electrode at 2000 r / min and heat it in a vacuum oven at 80°C for 2 h to obtain an active layer.
[0088] 4. Add 300 mg of PVDF-HFP to a glass bottle containing 3 ml of acetone and heat at 40°C with a magnetic stirrer at 1000 r / min for 2 hours to make it dissolve evenly, then add 832 μl of BMIM TFSI solution with a concentration greater than 99%, continue stirring at 1000 r / min for 1.5 hours, add 3 mg of (2,3,5,6-tetrafluoro-2,5-cyclohexadiene-1,4-diylidene) dimalononitrile to the solution and stir at 1000 r / min for 2 hours. Pour the prepared mixed liquid into a glass dish with a diameter of 35 mm, wrap it with tin foil, place it on a heating table and heat it at 45°C for 12 hours to gel, and obtain a doped ion gel layer, which is then adhered to the active layer obtained in step 3 with organic silica gel.
[0089] 5. Prepare a NaCl solution with a concentration of 0.1 mol / L, with water as the solvent, and place the device spin-coated in step 4 into the solution.
[0090] 6. Evaporate 60nm thick Au as the gate electrode and insert it into the electrolyte.
[0091] 7. Use a semiconductor analysis tester to test the performance of the device, set the drain voltage to -0.5V, and the gate voltage to 0.2V~-1V. The device performance obtained by the test is: transconductance g m =57.8mS, threshold voltage V t =0.33V, switch off I on / off =3.43×10 6 The device can operate for a long time (30000s) and can be stored for a long time (90 days transconductance retention 73%).
[0092] Example 5
[0093] This embodiment provides a method for preparing an organic electrochemical transistor based on a hydrophobic polymer. The difference from Example 3 and Example 4 is that the dosage of the dopant is adjusted to 9 mg. The specific steps are as follows:
[0094] 1. Cut the PET substrate into 10*20mm size and put it into the cleaned beaker, rinse it with deionized water twice, and ultrasonicate it for 10 minutes, then rinse it with acetone once and ultrasonicate it for 10 minutes, then rinse it with isopropanol once and ultrasonicate it for 10 minutes, finally blow it dry with a nitrogen gun, and heat and dry it at 80℃ for 30 minutes.
[0095] 2. Use vacuum deposition to deposit 60nm thick Au on the cleaned PET as source and drain electrodes at a deposition rate of
[0096] 3. Place the hydrophobic polymer PDPPBT in a glass bottle filled with chloroform and stir to prepare a solution with a concentration of 4 mg / ml to make it dissolve evenly. Then spin coat 20 μl of it on the prepared electrode at 2000 r / min and heat it in a vacuum oven at 80°C for 2 h to obtain an active layer.
[0097] 4. Add 300 mg of PVDF-HFP to a glass bottle containing 3 ml of acetone and heat at 40°C with a magnetic stirrer at 1000 r / min for 2 hours to make it dissolve evenly, then add 832 μl of BMIM TFSI solution with a concentration greater than 99%, continue stirring at 1000 r / min for 1.5 hours, add 9 mg of (2,3,5,6-tetrafluoro-2,5-cyclohexadiene-1,4-diylidene) dimalononitrile to the solution and stir at 1000 r / min for 2 hours. Pour the prepared mixed liquid into a glass dish with a diameter of 35 mm, wrap it with tin foil, place it on a heating table and heat it at 45°C for 12 hours to gel, and obtain a doped ion gel layer, which is then adhered to the active layer obtained in step 3 with organic silica gel.
[0098] 5. Prepare a NaCl solution with a concentration of 0.1 mol / L, with water as the solvent, and place the device spin-coated in step 4 into the solution.
[0099] 6. Evaporate 60nm thick Au as the gate electrode and insert it into the electrolyte.
[0100] 7. Use a semiconductor analysis tester to test the performance of the device, set the drain voltage to -0.5V, and the gate voltage to 0.2V~-1V. The device performance obtained by the test is: transconductance g m =43.9mS, threshold voltage V t =0.42V, switch off I on / off =3.19×10 5 , and the device can be stored for a short period of time.
[0101] Example 6
[0102] This embodiment provides a method for preparing a high-stability organic electrochemical transistor based on a hydrophobic polymer. The difference from Example 4 is that 300 mg of LiTFSI is added to the doped ion gel. The specific steps are as follows:
[0103] 1. Cut the PET substrate into 10*20mm size and put it into the cleaned beaker, rinse it with deionized water twice, and ultrasonicate it for 10 minutes, then rinse it with acetone once and ultrasonicate it for 10 minutes, then rinse it with isopropanol once and ultrasonicate it for 10 minutes, finally blow it dry with a nitrogen gun, and heat and dry it at 80℃ for 30 minutes.
[0104] 2. Use vacuum deposition to deposit 60nm thick Au on the cleaned PET as source and drain electrodes at a deposition rate of
[0105] 3. Place the hydrophobic polymer PDPPBT in a glass bottle filled with chloroform and stir to prepare a solution with a concentration of 4 mg / ml to make it dissolve evenly. Then spin coat 20 μl of it on the prepared electrode at 2000 r / min and heat it in a vacuum oven at 80°C for 2 h to obtain an active layer.
[0106] 4. Add 300 mg of PVDF-HFP to a glass bottle containing 3 ml of acetone and stir at 40°C for 2 hours with a magnetic stirrer at 1000 r / min to make it dissolve evenly. Add 300 mg of LiTFSI to the solution, stir at 40°C for 2 hours at 1000 r / min, then add 832 μl of BMIM TFSI solution with a concentration greater than 99%, continue stirring at 1000 r / min for 1.5 hours, then add 3 mg of (2,3,5,6-tetrafluoro-2,5-cyclohexadiene-1,4-diylidene) dimalononitrile to the solution and stir at 1000 r / min for 2 hours. Pour the prepared mixed liquid into a glass dish with a diameter of 35 mm, wrap it with tin foil, place it on a heating table, heat it at 45°C for 12 hours, and prepare a doped ion gel layer, which is adhered to the active layer obtained in step 3 with organic silica gel.
[0107] 5. Prepare a NaCl solution with a concentration of 0.1 mol / L, with water as the solvent, and place the device spin-coated in step 4 into the solution.
[0108] 6. Evaporate 60nm thick Au as the gate electrode and insert it into the electrolyte.
[0109] 7. Use a semiconductor analysis tester to test the performance of the device, set the drain voltage to -0.5V, and the gate voltage to 0.2V~-1V. The device performance obtained by the test is: transconductance g m =35.0mS, threshold voltage V t =0.26V, switch off I on / off =1.07×10 6 , and the device can be stored for a short period of time.
[0110] Example 7
[0111] This embodiment provides an application of a high-stability organic electrochemical transistor based on a hydrophobic polymer in the field of glucose sensing. After the gate electrode is modified with PDPPBT-doped nanoparticles / GOx / Nafion, the device is used for glucose concentration detection. The specific steps are as follows:
[0112] 1. Cut the PET substrate into 10*20mm size and put it into the cleaned beaker, rinse it with deionized water twice, and ultrasonicate it for 10 minutes, then rinse it with acetone once and ultrasonicate it for 10 minutes, then rinse it with isopropanol once and ultrasonicate it for 10 minutes, finally blow it dry with a nitrogen gun, and heat and dry it at 80℃ for 30 minutes.
[0113] 2. Use vacuum deposition to deposit 60nm thick Au on the cleaned PET as source and drain electrodes at a deposition rate of
[0114] 3. Place PDPPBT in a glass bottle filled with chloroform and stir to prepare a 4 mg / ml solution to dissolve it evenly. Then spin coat 20 μl of the solution at 2000 r / min on the prepared electrode and heat it in a vacuum oven at 80°C for 2 h to obtain an active layer.
[0115] 4. Add 300 mg of PVDF-HFP to a glass bottle containing 3 ml of acetone and heat at 40°C with a magnetic stirrer at 1000 r / min for 2 hours to make it dissolve evenly, then add 832 μl of BMIM TFSI solution with a concentration greater than 99%, continue stirring at 1000 r / min for 1.5 hours, add 3 mg of (2,3,5,6-tetrafluoro-2,5-cyclohexadiene-1,4-diylidene) dimalononitrile to the solution and stir at 1000 r / min for 2 hours. Pour the prepared mixed liquid into a glass dish with a diameter of 35 mm, wrap it with tin foil, place it on a heating table and heat it at 45°C for 12 hours to gel, and obtain a doped ion gel layer, which is then adhered to the active layer obtained in step 3 with organic silica gel.
[0116] 5. Place the device spin-coated in step 4 into a PBS buffer solution with the specifications of 10×, 0.1M, PH 7.2-7.4.
[0117] 6. Evaporate 60nm thick Au as the gate electrode and 8mg of MnO 2 Nanoparticles and 4 mg of PDPPBT were added to 1 ml of chloroform and ultrasonically treated for 40 min. Then, 50 μl was spin-coated on the gate electrode at 4000 r / min for 60 s and heated at 80 °C for 1 h. 20 μl of 20 mg / ml glucose oxidase aqueous solution was drop-cast on the heated gate electrode and heated at 37 °C for 1 h. Then, 10 μl of 5% Nafion solution was drop-cast on it and heated at 37 °C for 1 h to obtain the modified PDPPBT-doped nanoparticles / GOx / Nafion gate electrode and insert it into the PBS buffer solution in step 5.
[0118] 7. The sensing performance of the device was tested with a semiconductor analysis tester. The drain voltage was set to -0.5V, the gate voltage was set to -0.4V, and glucose solutions of different concentrations were prepared in PBS buffer. During the glucose sensing process, glucose solutions of different concentrations were added to change the glucose concentration in the environment. The corresponding source-drain current responses at test concentrations of 1nM, 5nM, 10nM, 100nM, 1μM, 10μM, 100μM, 250μM, 500μM, 1mM, and 10mM were recorded. The results are shown in Table 1:
[0119] Table 1
[0120]
[0121] The device can detect glucose concentrations with a lower limit of 1nM and a detection range of 1nM to 10mM. Figure 7 shown.
[0122] Compared with the organic electrochemical transistor based on hydrophilic polymer (i.e., the electrochemical transistor prepared in Example 2-5), the overall performance of the device, such as transconductance and switch ratio, has been greatly improved by introducing the organic electrochemical transistor (i.e., the electrochemical transistor prepared in Example 1) with hydrophobic polymer. This is because the hydrophilic side chain in the hydrophilic polymer can absorb water molecules from the air and capture charges, thereby reducing the problem of the organic electrochemical transistor transconductance, cycle test stability and storage stability caused by the reduced charge transfer capacity and stability. The organic electrochemical transistor prepared based on hydrophobic polymer and doped ion gel (i.e., the electrochemical transistor prepared in Example 3-5) has a further improvement in performance compared with the organic electrochemical transistor prepared based on traditional ion gel (i.e., the electrochemical transistor prepared in Example 2). This is because the ion gel dopant acts on the ion gel, which can improve the coordinated transmission of electrons and ions, increase the conduction path of electrons, and improve the electron mobility, thereby improving the carrier injection efficiency and conductivity, and then improving the transconductance performance of the device. In addition, the ion gel dopant can enhance the chemical stability and durability of the ion gel, especially under long-term operation conditions, improve the long-term stability and reliability of the device, and greatly optimize the comprehensive performance of the device. m ) reaches 57.8mS, the threshold voltage (V t ) is 0.33V, the switch ratio (I on / off ) is 3.43×10 5 At the same time, the device's cycle test stability reaches 30,000s and has the ability to be stored for a long time (90 days).
[0123] By modifying the gate of a high-stability organic electrochemical transistor based on a hydrophobic polymer (such as the modification process in Example 7), the charge transfer efficiency and device sensitivity of the electrode are enhanced, and the modified device is used for glucose sensing, detection of ultra-low glucose concentrations with a lower limit of 1 nM can be achieved.
[0124] Note: The above examples are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements that do not depart from the spirit and scope of the present invention should be covered by the scope of the claims of the present invention.
Claims
1. An organic electrochemical transistor based on a hydrophobic polymer, characterized in that: The invention comprises a substrate, a source electrode, a drain electrode, a hydrophobic active layer, a doped ion gel layer, an electrolyte layer and a gate electrode. The hydrophobic active layer contains a hydrophobic polymer, and the doped ion gel layer contains a gel polymer, an ionic liquid and a dopant.
2. The organic electrochemical transistor according to claim 1, characterized in that The mass ratio of the gel polymer to the dopant in the doped ion gel layer is 1200-30:1, and the dosage ratio of the gel polymer to the ionic liquid is 300-400 mg:1 ml.
3. The organic electrochemical transistor according to claim 1, characterized in that The doped ion gel layer further contains bis(trifluoromethylsulfonyl)imide salt, and the mass ratio of the bis(trifluoromethylsulfonyl)imide salt to the gel polymer is 0.8-1.5:
1.
4. The organic electrochemical transistor according to any one of claims 1 to 3, characterized in that When applied to glucose sensing, the gate is coated with PDPPBT doped with nanoparticles, drop-cast glucose oxidase GOx and drop-cast Nafion in sequence.
5. A method for preparing an organic electrochemical transistor based on a hydrophobic polymer, characterized in that the steps include: S1: Using vacuum deposition method, evaporate the source and drain electrodes on the surface of the substrate; S2: Spin-coating a hydrophobic polymer solution on the source and drain electrodes, and heat treating the solution to obtain a hydrophobic active layer; S3: mixing the gel polymer, the ionic liquid and the dopant in an organic solvent, and heat treating the mixture to obtain a doped ion gel layer; adhering the doped ion gel layer to the hydrophobic active layer prepared in step 2 to obtain a device; S4: using vacuum deposition method to evaporate the gate; S5: placing the device prepared in step S3 and the gate prepared in step S4 in an electrolyte.
6. The preparation method according to claim 5, characterized in that: In S3, the organic solvent further contains bis(trifluoromethylsulfonyl)imide salt.
7. The preparation method according to claim 5 or 6, characterized in that: When applied to glucose sensing, in S4, a solution of doped nanoparticles and PDPPBT is spin-coated on the gate and heat-treated; then a glucose oxidase aqueous solution is drop-cast and heat-treated; finally, a Nafion solution is drop-cast and heat-treated to prepare a gate electrode modified with PDPPBT doped nanoparticles / GOx / Nafion.
8. The organic electrochemical transistor according to any one of claims 1 to 4 or the organic electrochemical transistor prepared by the preparation method according to any one of claims 5 to 7 is used for preparing a sensor or a sensor for qualitative and / or quantitative detection of glucose.
9. A sensor, characterized in that: An organic electrochemical transistor comprising the organic electrochemical transistor according to any one of claims 1 to 4 or an organic electrochemical transistor prepared by the preparation method according to any one of claims 5 to 7.
10. A method for qualitative and / or quantitative detection of glucose, comprising: The organic electrochemical transistor according to any one of claims 1 to 4 or the organic electrochemical transistor prepared by the preparation method according to any one of claims 5 to 7 is placed in a buffer solution not containing glucose, the response of the source and drain electrodes is recorded, and then the sample solution is added, the response change of the source and drain electrodes is recorded, and qualitative and / or quantitative detection of glucose is performed.
Citation Information
Patent Citations
High-performance organic electrochemical transistor of foam structure channel prepared based on template sacrifice method and preparation method and application thereof
CN116660353A
Preparation method and application of D-A type conjugated polymer
CN118812826A